Philosophy in the context of our time – IV: The perennial question concerning “(metaphysical) categories” - Strauss, D. F. M. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
In response to the contribution of Heinrich Alt to my Festschrift (see Alt, 2006), this article focuses on the human ability to discern. This ability generated all kinds of classificatory schemes throughout the history of philosophy. The different categories introduced by philosophers such as Aristotle, the transcendentalia of Thomas Aquinas, Kant and Hartmann provide examples of “metaphysical” schemes, that is to say, schemes without sufficient ontic foundations. After some immanentcritical remarks an alternative approach is articulated, the transcendental-empirical method. This method enables an analysis of those conditions making possible what we can experience. The two ontic dimensions implied in applying this transcendental-empirical method, namely those of aspects and entities, first of all need an established terminology. At the same time an account is required of the difference between (unspecified) modal laws and (specified) type-laws (the latter was not accepted by Vollenhoven). Ten criteria, applicable in discerning different modal aspects of reality, are articulated in support of the transcendental-empirical thrust underlying this theory of modal law-spheres, a theory that is indeed unique in the history of philosophy. A number of issues surface the moment a philosopher starts to contemplate different ways to design categories aimed at an understanding of the universe in which we live. Executing such a task inevitably runs into a number of related issues. Some of the most important ones are analyzed in the contribution of Heinrich Alt to my Festschrift – under the title “The problem of universals” (see Alt, 2006). He pays attention to the distinction between tokens and types, between attributes and the class of entities exemplifying them, resemblance, the idea of a substance underlying attributes (pro perties) as opposed to the notion of a bundle and the relation between the subject, the distinction between and predicate of a statement and that of universality and individuality.